STRENGTHENING PROGRAM FOR NUCLEAR CYBER SECURITY AT NUCLEAR FACILITIES - Dikdik Sidik Purnama; Mokhamad Hendayun; Barito Mulyo Ratmono; Poppy Setiawati Nurisnaeni; Satriani Aga Pasma; Rahmat Khatib Purnama (HIMNI, 2022)
Threats to the safety and security aspects of a facility target the physical aspects and the cyberinfrastructure. Critical facilities such as nuclear facilities use cyber-physical systems in their operating systems has vulnerabilities. Nuclear facilities in Indonesia could become targets of cyberterrorism because there have been incidents of attacks in several countries related to nuclear terrorism for specific purposes that threaten the safety and security operations of nuclear facilities. Similar threats may occur at other nuclear facilities as well as nuclear facilities in Indonesia, including the nuclear facility in Indonesia. The purpose of this study is to propose a nuclear cybersecurity program with a qualitative approach to attract more attention in supporting the anticipation of increasing cybersecurity threats at nuclear facilities. The program proposed was based on the description of terminology in nuclear safety and security and literature studies describing incidents of nuclear cyberterrorism attacks in the past. A cyber nuclear security program has been proposed through stakeholder collaboration, resource support, and capacity building for the ongoing nuclear security program.